Wonder cloth - WINTERS, Jeffrey (Mechanical engineering (New York, N.Y. 1919), 2006)
Developed at the University of Texas at Dallas, a filmy, very strong material may well be the first breakthrough in bringing carbon nanotubes to the mass market. Ever since they were first discovered in 1991, carbon nanotubes have been the subject of intense speculation about what they may eventually be able to do. Materials scientists have known that carbon-based molecules had the potential to possess extreme properties. As the liquid flowed, the nanotubes aligned themselves along the direction of the flow. When dried, the resulting fibers were flexible, but the researchers could not find a way to make them very strong. It is not just the mechanical properties that make the nanotube fabric a supersheet. The pure carbon membrane turned out to be a very flexible conductor of electricity. Such properties open up a number of possibilities. The extraordinary strength and lightness of the nanotube sheets suggest they could first find use in high-end applications such as military aircraft or motor sports.